2014
DOI: 10.1007/s40471-014-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Achieving and Maintaining Cardiovascular Health Across the Lifespan

Abstract: The American Heart Association introduced the concept of cardiovascular health (CVH) in its 2020 Strategic lmpact Goals. Defined by the presence of four health behaviors (smoking, weight, diet, and physical activity) and three health factors (glucose, blood pressure, and cholesterol), CVH reflects an expansion of preventive efforts to the entire population and a reframing of disease prevention to health promotion. Recent evidence has confirmed the relevance of the seven CVH metrics in cardiovascular outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Second, our sample only included people from the fifth decade of their life onward. In the light of our results and given that VRFs typically develop earlier in life (Karmali & Lloyd-Jones, 2014;Lloyd-Jones et al, 2010), more research including young and young middle-aged adults is needed to elucidate when precisely the observed associations arise. Third, we operationalized some VRFs by combining self-reported clinical diagnosis with laboratory assessments.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…Second, our sample only included people from the fifth decade of their life onward. In the light of our results and given that VRFs typically develop earlier in life (Karmali & Lloyd-Jones, 2014;Lloyd-Jones et al, 2010), more research including young and young middle-aged adults is needed to elucidate when precisely the observed associations arise. Third, we operationalized some VRFs by combining self-reported clinical diagnosis with laboratory assessments.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…5e12). A growing number of scientific studies have demonstrated the favourable effects of low-to-moderate intensity physical activity (PA) on cardiometabolic health (Karmali & Lloyd-Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The search began with a combination of terms in the following three categories: 1) health behaviors and indicators, 2) technologies, and 3) behavioral theories ( Table 1 ). The health behaviors and relevant indicators were congruent with the key cardiovascular health metrics defined by the AHA in 2010 [5] and included the following: physical activity (PA), weight management, tobacco use, blood glucose, blood pressure and lipids. To gain the broadest understanding of the current state of the science in this field, a comprehensive array of terms was included for technologies, including mobile, social media, wearables, and other Internet-based terms.…”
Section: Methodsmentioning
confidence: 99%